Oscillation Detection Of A Quadrotor System Carrying Suspended Payload Using Image Processing Technique - Noor Hanis Izzuddin Mat Lazim; Liyana Ramli; Amalin Aisya Mohd Awi; Zaharuddin Mohamed; H.I Jaafar (Penerbit UMT, 2024)
Indexed by ERA/MYCITE